2006
DOI: 10.1266/ggs.81.219
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome-linked genes in plants

Abstract: Recent studies of plant sex chromosome-linked genes have revealed many interesting characteristics, although there are limited reports about heteromorphic sex chromosomes in flowering plants. Sex chromosome-linked genes in angiosperms have been characterized mainly in the dioecious plant Silene latifolia . Although all such genes were isolated from transcripts of male flower buds of S. latifolia , most seem to be housekeeping genes except for the petal-and stamen-specific MADS box gene on the Y chromosome ( Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 76 publications
2
21
0
1
Order By: Relevance
“…It is not certain whether the SlCypX gene is on the Xp or Xq arm; if the former, further rearrangements would be necessary to move this gene close to the Su F gene. Although the locations of the SlY4, SlY3, SlY7, and SlY8 genes are somewhat uncertain, they are clearly not near the Su F gene and can all be assigned to the Yq arm, supporting the previous conclusions about SlY4 and SlY3 and inference of a pericentric inversion (Zluvova et al 2005a;Matsunaga 2006;Hobza et al 2007). However, in all three sets of deletion strains two deletions are needed to explain the absence of the SlY3 and SlY7 markers in some hermaphrodites.…”
Section: Resultssupporting
confidence: 67%
“…It is not certain whether the SlCypX gene is on the Xp or Xq arm; if the former, further rearrangements would be necessary to move this gene close to the Su F gene. Although the locations of the SlY4, SlY3, SlY7, and SlY8 genes are somewhat uncertain, they are clearly not near the Su F gene and can all be assigned to the Yq arm, supporting the previous conclusions about SlY4 and SlY3 and inference of a pericentric inversion (Zluvova et al 2005a;Matsunaga 2006;Hobza et al 2007). However, in all three sets of deletion strains two deletions are needed to explain the absence of the SlY3 and SlY7 markers in some hermaphrodites.…”
Section: Resultssupporting
confidence: 67%
“…The evolutionary events that led to the emergence of the Y chromosome are more complex than those for the X chromosome because multiple rearrangements have occurred entirely on the Y chromosome (Matsunaga 2006, Jamilena et al 2008. Mapping of the Y chromosome has been performed primarily by genotyping Y-deletion mutants using Y-linked genetic markers (Zluvova et al 2005, Bergero et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Various genomic approaches have been exploited to isolate sex chromosome-linked genes involved in sex determination and flower development in S. latifolia, including segregation analysis of random genes (Guttman andCharlesworth 1998, Filatov 2005), screening of a male flower cDNA library with microdissected Y-specific probes (Delichère et al 1999, Atanassov et al 2001, differential displays applied to male and female flower buds , Matsunaga et al 2005, and segregation analysis of intron size variants (Bergero et al 2007). Twelve sex chromosome-linked genes (MROS3X,SlMF1,SlX/Y1,SlX/Y4,DD44X/Y,SlX/Y3,SlssX/Y,SlCypX/Y,SlX/Y6a,SlX/Y6b,SlX/Y7,SlAP3Y) have been identified to date (Matsunaga 2006, Jamilena et al 2008. Matsunaga et al (2003) reported that SlAP3Y and its autosomal counterpart, SlAP3A, exhibit significant similarities to APETALA3, which functions in determining the identities of petals and stamens in Arabidopsis thaliana (Jack et al 1992).…”
mentioning
confidence: 99%
“…1 ). The family RAE180, which is also located in a single autosomal locus, is a major component of both the Y 1 and Y 2 chromosomes (Shibata et al, 2000), while the family RAYSI is specific to the Ys of R. acetosa (Shibata et al, 1999) and other related species with a multiple sex chromosome system (XX/XY 1 Y 2 ), including R. papillari s, R. intermedius , R. thyrsoides and R. tuberosus (Navajas-Perez et al, 2005b, 2006. The evolution of these Y chromosome satellite DNAs in the non-recombining Y of R. acetosa , with a reduced rate of concerted evolution, has produced a diversification of satellite DNAs in different subfamilies and families.…”
Section: Tandem Satellite Dnamentioning
confidence: 99%